ANALISIS FENOMENA SOSIAL PADA SISWA SD NEGERI 2 DESA SANDING DI DALAM PROSES BELAJAR MENGAJAR - Mohammad Irfan Farraz Haecal (Peksos: Jurnal Ilmiah Pekerjaan Sosial, 2022)
The objective of this study was to assess the effectiveness of material absorption in the teaching and learning process for students at SD Negeri 2 Sanding. The research employed a qualitative method and utilized direct observation during field research activities. This research shows that students have an improved ability to comprehend the presented material compared to conventional methods. Occasionally, both parties may come to a conclusion or express dissatisfaction with the other party's content. However, one can still learn from these situations and determine their own attitude. This study suggests further research due to the short duration of the study.